Sustainable potato production. Guidelines for developing countries. - Lutaladio, N.; Ortíz, O.; Haverkort. A.; Caldiz, D. (Food and Agriculture Organization of the United Nations, 2009)
These guidelines present a compilation of potato management practices in use in tropical and subtropical developing countries that have helped increase potato production and productivity. They can be refined to address particular conditions in specific locations. The publication provides indicators of sustainability, and highlights potential areas of improvement for potato development. While aimed primarily at decision makers, the manual tries as much as possible to use language familiar to farmers.